Analisis User Satisfaction pada Sistem Informasi Keuangan Terpadu Yayasan Pendidikan Teknik Purbalingga Berbasis Web (Smart-YPT) Menggunakan Pendekatan User Experience - Muh Sofi'i; Wika Purbasari (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2018)
Smart-YPT is an Integrated FinancialInformation System Integrated Financial InformationSystem of WEB-Based Purbalingga TechnicalEducation Foundation which is applied to businessunit within Environmental Purbalingga EducationalFoundation. In this research, system user satisfactionanalysis (Smart-YPT) with independent variables are:Content, Usefullness, Ease of Use and Ease of Learning. T test results from 70 respondents Smart-YPT users using SPSS, with the value of t table 1.66865 proved that there is a significant influence ofvariable Content, Usefullness, Ease of Use of UserSatisfaction, because it has a value of t arithmeticgreater than 1.66865 . While for Ease of Learningvariable proved no significant effect on UserSatisfaction because it has t count equal to 0,570(under 1.66865). From Test F, 4 (four) variablesstudied proved to have a significant effect on UserSatisfaction, because value F arithmetic of 20.808 isgreater than F table (2.51).